Penyuluhan Hukum Pencegahan Tindak Pidana Narkotika dan Bantuan Hukum di Desa Pasayangan - Rita Kurnia; Elsa Nurridha Indryati; Berlian Mahadewi; Furqon Yohana Alfiansyah; Nurul Misbah; Muhammad Fakhri; Iman Jalaludin Rifai; Bias Lintang Dialog; Dikha Anugrah (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Rural communities are vulnerable to narcotics abuse, because a lack of understanding of the dangers of narcotics makes them easily influenced by narcotics dealers. The population in Pasayangan Village, Lebakwangi District, Kuningan Regency is quite large, consisting of 11 RTs. There are also many people who do not know about legal Assistance, on average they are still confused about how and where they can seek legal assistance in the event of a criminal case, especially legal Assistance for underprivileged people. To anticipate that people are not involved in narcotics abuse, legal counseling is needed, especially in preventing narcotics crime and secondly legal assistance. Problems with lack of understanding such as the Narcotics Law, forms of narcotics prevention, and procedures for seeking legal assistance. The purpose of this activity is to increase the insight and knowledge of the community. As for the stages of implementing community partnership program activities with preparation, implementation of activities, evaluation and reporting. Community service activities in the form of outreach and legal counseling received a very positive response from the participants. The emergence of an understanding of the people of Pasayangan Village, Lebakwangi District, Kuningan Regency, especially being able to understand the dangers of narcotics abuse, being able to understand Law Number 35 of 2009 concerning Narcotics, Forms of Prevention of the Spread and Abuse of Narcotics, and Legal Assistance Procedures for Underprivileged Communities.